2017
DOI: 10.1002/ecs2.1853
|View full text |Cite
|
Sign up to set email alerts
|

Toward an improved conceptual understanding of North American tree species distributions

Abstract: Abstract. Species distributions have often been assumed to represent climatic limitations, yet recent evidence has challenged these assumptions and emphasized the potential importance of biotic interactions, dispersal limitation, and disturbance. Despite significant investigation into these factors, an integrated understanding of where and when they may be important is lacking. Here, we review evidence for the factors underlying the historical and contemporary distributions of North American tree species and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 249 publications
(721 reference statements)
1
17
0
Order By: Relevance
“…While these findings do not directly support our initial hypothesis regarding variation in the relative importance of climate and biotic interactions across elevational gradients, lower model performance among lower‐elevation montane species does indicate that climate contributes more strongly to the distributions of high‐elevation species, and alternative non‐climatic processes may operate more strongly at lower elevations. Overall, our findings are in agreement with many other studies that have identified climate as an important driver of North American tree distributions and that have found limited evidence for a strong, independent influence of alternative processes including biotic interactions (reviewed in Copenhaver‐Parry, Shuman, & Tinker, ).…”
Section: Discussionsupporting
confidence: 92%
“…While these findings do not directly support our initial hypothesis regarding variation in the relative importance of climate and biotic interactions across elevational gradients, lower model performance among lower‐elevation montane species does indicate that climate contributes more strongly to the distributions of high‐elevation species, and alternative non‐climatic processes may operate more strongly at lower elevations. Overall, our findings are in agreement with many other studies that have identified climate as an important driver of North American tree distributions and that have found limited evidence for a strong, independent influence of alternative processes including biotic interactions (reviewed in Copenhaver‐Parry, Shuman, & Tinker, ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the abundance and distribution of a species can be strongly shaped by competitive interactions, particularly at local to landscape scales (Copenhaver‐Parry et al. ), and process‐based models are a promising tool for determining where and why interspecific biotic interactions might modulate how tree species respond to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…While our approach takes a step beyond climate suitability studies by considering the processes that are important during a sensitive life-history stage (regeneration), we still only consider the responses of individual tree species to changing climate and fire. However, the abundance and distribution of a species can be strongly shaped by competitive interactions, particularly at local to landscape scales (Copenhaver-Parry et al 2017), and process-based models are a promising tool for determining where and why interspecific biotic interactions might modulate how tree species respond to climate change.…”
Section: What Causes Regeneration Failure (Or Success?)mentioning
confidence: 99%
“…Additionally, assessments of mismatch can be sensitive to which variables are included in models. We focused on responses to soil water because of its importance for trees in this region, and across North America (Copenhaver‐Parry et al ), however other environmental variables may be uniquely important for different species. We chose to model all of the species with the same predictors to enable better comparisons.…”
Section: Discussionmentioning
confidence: 99%